KONSEP ISLAM DALAM FITRAH LINGKUNGAN KELUARGA DAN PENDIDIKAN SEUMUR HIDUP - Azis, Rosmiaty (Universitas Islam Negeri Alauddin Makassar, 2020)
In its implementation, it is the parents who are responsible for education in the family environment or in the household: teachers and school administrators including the government as the person in charge of education in the school environment: community leaders and others as the person in charge of education in the community. These three parties each have their own educational responsibilities in their respective environments, but that does not mean that they are only fully responsible for their environment. but also have significant responsibilities in other educational settings. Parents, for example, are responsible for education in the family environment. but this responsibility is not only limited to the household environment, but also requires responsibility within the school and community environment.